Sociological application of behavioural theories to work performance of academic staff in Nigerian universities - Oladejo, Segilola Yewande; Adenuga, Ademolu Oluwaseun (Przegląd Krytyczny, 2023)
Several authors have researched workplace circumstances and employee performance in organisations. Personal observations, documented observations, and discoveries in the literature all provided an incentive for this investigation. Some systematic observations revealed that academic staff in Nigerian universities are subjected to some unfavourable workplace conditions, even though they are expected to perform well in teaching, publish quality research papers that can contribute to global knowledge and development, and engage in community development services. Major theories have attempted to explain employee productivity in the workplace. Using secondary data, this article explores the Two Factor model by Fredrick Herzberg, the Contingency theory of leadership and the Expectancy theory by Victor Vroom. They were most relevant in associating motivating factors with the work performance of employees in the organisation. The criticisms of each theory have paved the way for theoretical triangulation and, thus, a synthesis of all three theories to explain the work performance of academic staff members in Nigerian universities. The article resolved that incentives are indeed essential in order to increase the performance of academic staff in Nigerian universities.